Cu-based nano array catalyst as well as preparation method and application thereof

By depositing Cu on the gas diffusion electrode and forming a Cu(OH)2/Cu heterostructure, and combining steam reduction, Cu-based nanoarray catalyst was prepared, which solved the problem of difficulty in maintaining the morphology of Cu/Cu2O heterostructure in the prior art, and achieved a high selectivity and active CO2 reduction catalytic effect.

CN119615257APending Publication Date: 2025-03-14NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795945.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the morphology of the catalyst on the basis of forming a Cu/Cu2O heterostructure, resulting in low selectivity of C2+ products.

Method used

Cu was deposited on the gas diffusion electrode by electrodeposition method, and Cu(OH)2 was synthesized on the Cu layer by in-situ growth method to form a heterostructure of Cu(OH)2/Cu, and then the Cu-based nanoarray catalyst was reduced by steam method.

Benefits of technology

The formation of Cu0/Cu1+ heterogeneous interface was achieved, which improved the selectivity of ethylene by 56%, maintained the overall morphology of the catalyst, and improved the current density and catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615257A_ABST
    Figure CN119615257A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalytic reduction, and discloses a Cu-based nano array catalyst and a preparation method and application thereof. The preparation method comprises the following steps: depositing Cu on a gas diffusion electrode by adopting an electro-deposition method, forming a Cu (OH) 2 / Cu nano array with a heterostructure by utilizing an in-situ growth method, further, partially reducing Cu (OH) 2 into Cu2O through hydrazine hydrate steam to obtain a Cu (OH) 2 (at) Cu2O nano array with a core-shell structure, and forming a 3D hierarchical Cu (OH) 2 (at) Cu2O / Cu nano array by the Cu (OH) 2 (at) Cu2O core-shell structure and a Cu substrate. The unique Cu0 / Cu1 + heterojunction surface obviously improves the performance of the catalyst, realizes the ethylene selectivity up to 56%, and shows excellent catalytic activity and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic reduction, and in particular to a Cu-based nano-array catalyst and a preparation method and application thereof. Background Art

[0002] Producing multicarbon (C 2+ ) products, which can not only reduce greenhouse gas emissions, but also realize the storage and conversion of renewable energy, providing an important way. Compared with the research on C1 products, more advanced C2 products, such as ethylene (C2H4), are products with higher added value. Copper-based materials are currently used to produce C 2+ The most effective catalyst for the production of C2H4. Due to the extremely high industrial value and limited sources of C2H4, the direction of high current density and Faradaic efficiency (FE) CO2 RR to produce C2H4 has been intensively studied. However, since the formation of C2H4 involves multi-step electron and proton transfer processes, hydrogen (H2) and other by-products will inevitably be produced during the electrolysis process, and the selectivity and activity of Cu-based catalysts in producing C2H4 are still limited.

[0003] At present, relevant studies have shown that in the electrocatalytic CO2 reduction reaction, Cu 0 and Cu 1+ The balance of Cu is crucial for the conversion of CO2 to C2H4. 0 The Cu 1+ The position enhances the adsorption of *CO, promotes CC coupling, and effectively generates C2H4. In the method of regulating the oxidation state of the catalyst, it is usually synthesized by thermal oxidation, followed by H2 or inert gas annealing or in situ electrolytic reduction. Liu et al. (Liu W, Zhai P, Li A, et al. Electrochemical CO2 reduction to ethylene by ultrathin CuO nanoplate arrays[J]. Nature communications, 2022, 13(1): 1877.) proposed a method for electrochemical regulation of the oxidation state and successfully synthesized oxygen-rich ultrathin CuO nanoplate arrays. These arrays formed a Cu / Cu2O heterogeneous interface through self-evolution during the electrocatalytic process. It effectively improved the efficiency and stability of CO2 reduction to ethylene. However, the above electrochemical method may damage the morphology of the catalyst, resulting in Cu 0 / Cu 1+The disappearance of the heterogeneous interface limits its applicability on different catalysts. Sun et al. (Sun M, Cheng J, Yamauchi M. Gas diffusion enhanced electrode with ultrathin superhydrophobic macropore structure for acidic CO2 electroreduction [J]. Nature communications, 2024, 15 (1): 491.) designed a Cu(OH)2 nanoneedle array structure in a porous copper foil, and then reduced Cu(OH)2 to obtain Cu-GDL by high temperature annealing in a H2 atmosphere, which showed high C in acidic electrolytes. 2+ Although the reduction of Cu(OH)2 nanowire arrays by high temperature annealing method can preserve their morphology compared with the electrochemical method, no Cu / Cu2O heterostructure is formed, which leads to the 2+ The product selectivity is low. Summary of the invention

[0004] The purpose of the present invention is to provide a Cu-based nanoarray catalyst and a preparation method and application thereof, so as to solve the problem that the existing preparation method cannot maintain the morphology of the catalyst on the basis of forming a Cu / Cu2O heterogeneous structure, thereby causing the Cu 2+ The problem of low product selectivity.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a Cu-based nanoarray catalyst, comprising the following steps:

[0007] (1) In a dual-electrode system, a gas diffusion electrode is electrodeposited in a copper salt-containing electrolyte to obtain a Cu-loaded gas diffusion electrode;

[0008] (2) immersing the Cu-loaded gas diffusion electrode of step (1) in a mixed solution of persulfate and strong alkali for in-situ growth to obtain a Cu(OH)2 / Cu heterostructure;

[0009] (3) The Cu(OH)2 / Cu heterostructure described in step (2) is reduced by a steam method using a reducing agent to obtain a Cu-based nanoarray catalyst.

[0010] Preferably, in the preparation method, the composition of the copper salt electrolyte in step (1) includes: CuSO4·5H2O, H2SO4, PVP, disodium EDTA and water; wherein the concentration of CuSO4·5H2O is 0.1-0.3 mol / L, the concentration of H2SO4 is 1-2 mol / L, the concentration of disodium EDTA is 10-30 mmol / L, and the concentration of PVP is 10-15 g / L.

[0011] Preferably, in the preparation method, the dual-electrode system in step (1) is: the gas diffusion electrode is the working electrode, and the copper mesh is the counter electrode.

[0012] Preferably, in the preparation method, the current of the electrodeposition in step (1) is 200 to 250 mA, and the time is 600 to 1000 s.

[0013] Preferably, in the preparation method, in the mixed solution of persulfate and strong base in step (2), the persulfate comprises potassium persulfate, ammonium persulfate or sodium persulfate, the strong base comprises sodium hydroxide or potassium hydroxide, and the molar ratio of the persulfate to the strong base is 1:35-50.

[0014] Preferably, in the preparation method, the temperature of the in-situ growth in step (2) is room temperature and the time is 10 to 15 minutes.

[0015] Preferably, in the preparation method, the reducing agent in step (3) comprises hydrazine hydrate or formaldehyde, and the volume concentration of the reducing agent is 50 to 80 vt%.

[0016] Preferably, in the preparation method, the temperature of the steam reduction in step (3) is 60 to 80° C. and the time is 15 to 60 minutes.

[0017] The invention also provides a Cu-based nano-array catalyst prepared by the preparation method.

[0018] The present invention also provides an application of the Cu-based nano-array catalyst in preparing C2H4 by electrocatalytic reduction of CO2.

[0019] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention deposits Cu on a gas diffusion electrode by an electrodeposition method, and then synthesizes Cu(OH)2 on the Cu layer by an in-situ growth method. The Cu(OH)2 is partially converted from the Cu on the Cu substrate to form a Cu(OH)2 / Cu heterostructure. The obtained Cu(OH)2 nanoneedles are sea urchin-shaped, with a length of 5 to 20 μm and a diameter of 100 to 300 nm. On the basis of obtaining the Cu(OH)2 / Cu heterostructure, the present invention reduces the Cu(OH)2 obtained by in-situ growth by a steam reduction method to obtain Cu(OH)2@Cu2O. The Cu(OH)2@Cu2O obtained by partial reduction by the steam reduction method does not destroy its original needle-like structure. The shell thickness of Cu2O is regulated by controlling the reduction time. When the reduction is 15 minutes, the optimal ratio of Cu(OH)2 and Cu2O core-shell is obtained. The Cu(OH)2@Cu2O core-shell structure and the Cu substrate form a 3D hierarchical Cu(OH)2@Cu2O / Cu nanoarray. Compared with Cu(OH)2, the overall morphology of Cu(OH)2@Cu2O nanoneedles remains intact. In addition, Cu(OH)2 will self-evolve to form Cu2O during the reduction process, and part of Cu2O will self-evolve to form Cu, thus forming Cu 0 / Cu 1+ Heterojunction interface, Cu 0 / Cu 1+ Under the synergistic effect of the above, the Cu-based nano-array catalyst prepared by the present invention can achieve 56% ethylene selectivity, as well as higher current density and better catalytic activity. The present invention adopts the above method to get rid of the use of binders in traditional powder catalysts. Compared with powder materials, the array-type catalyst prepared by the present invention has better electron-proton transmission ability and higher economic benefits.

[0021] (2) The process for preparing the Cu-based nanoarray catalyst of the present invention is simple, low-cost, requires simple equipment, and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0023] Figure 1 This is a SEM image of the Cu(OH)2 / Cu heterostructure in step (2) of Example 1;

[0024] Figure 2 This is the SEM image of Cu(OH)2@Cu2O / Cu-15 of Example 1;

[0025] Figure 3 The selectivity result of Cu(OH)2@Cu2O / Cu-15 to C2H4 in Example 1;

[0026] Figure 4 is the SEM image of Cu2O / Cu-60 of Example 2;

[0027] Figure 5 The selectivity result of Cu2O / Cu-60 to C2H4 in Example 2;

[0028] Figure 6 is the XRD pattern of the catalyst of Example 1;

[0029] Figure 7 The XRD patterns of the catalysts of Examples 1 to 4 are shown in FIG. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a Cu-based nanoarray catalyst, comprising the following steps:

[0031] (1) In a dual-electrode system, a gas diffusion electrode is electrodeposited in a copper salt-containing electrolyte to obtain a Cu-loaded gas diffusion electrode;

[0032] (2) immersing the Cu-loaded gas diffusion electrode of step (1) in a mixed solution of persulfate and strong alkali for in-situ growth to obtain a Cu(OH)2 / Cu heterostructure;

[0033] (3) The Cu(OH)2 / Cu heterostructure described in step (2) is reduced by a steam method using a reducing agent to obtain a Cu-based nanoarray catalyst.

[0034] In the present invention, the dual-electrode system in step (1) is preferably: the gas diffusion electrode is the working electrode (cathode), and the copper mesh is the counter electrode (anode).

[0035] In the present invention, the gas diffusion electrode is preferably single-sided hydrophobic carbon paper.

[0036] In the present invention, the gas diffusion electrode and the copper mesh preferably have the same area.

[0037] In the present invention, the composition of the copper salt electrolyte in step (1) includes: CuSO 4· 5H2O, H2SO4, PVP, disodium EDTA and water.

[0038] In the present invention, the CuSO 4· The concentration of 5H2O is preferably 0.1 to 0.3 mol / L, more preferably 0.1 to 0.2 mol / L, and even more preferably 0.2 mol / L.

[0039] In the present invention, the concentration of H2SO4 is preferably 1 to 2 mol / L, more preferably 1 to 1.5 mol / L, and more preferably 1.5 mol / L.

[0040] In the present invention, the concentration of disodium EDTA is preferably 10 to 30 mmol / L, more preferably 10 to 20 mmol / L, and more preferably 10 mmol / L.

[0041] In the present invention, the concentration of PVP is preferably 10 to 15 g / L, more preferably 10 to 12 g / L, and even more preferably 10 g / L.

[0042] In the present invention, the average molecular weight of the PVP is preferably 40,000 to 160,000, more preferably 50,000 to 100,000, and even more preferably 55,000.

[0043] In the present invention, the current of the electrodeposition in step (1) is preferably 200-250 mA, more preferably 220-250 mA, and more preferably 250 mA; the time is preferably 600-1000 s, more preferably 600-800 s, and more preferably 600 s; the electrodeposition is preferably carried out by a constant current method.

[0044] In the present invention, in the Cu-loaded gas diffusion electrode of step (1), the particle size of Cu is preferably 0.5 to 3 μm.

[0045] In the present invention, the Cu-loaded gas diffusion electrode in step (2) is preferably washed before impregnation.

[0046] In the present invention, the washing agent is preferably water.

[0047] In the present invention, the mixed solution of persulfate and strong base in step (2) is preferably a mixed aqueous solution of persulfate and strong base.

[0048] In the present invention, the method for preparing the mixed solution of persulfate and strong base in step (2) preferably comprises the following steps: mixing persulfate with water to obtain a first solution; mixing a strong base with water to obtain a second solution; adding the second solution to the first solution and mixing to obtain a mixed solution of persulfate and strong base.

[0049] In the present invention, the persulfate preferably comprises potassium persulfate, ammonium persulfate or sodium persulfate, further preferably comprises potassium persulfate or sodium persulfate, and more preferably is potassium persulfate.

[0050] In the present invention, the strong base preferably comprises sodium hydroxide or potassium hydroxide, and more preferably sodium hydroxide.

[0051] In the present invention, the concentration of the persulfate in the first solution is preferably 0.1 to 0.3 mol / L, more preferably 0.1 to 0.2 mol / L, and more preferably 0.2 mol / L.

[0052] In the present invention, the concentration of the strong base in the second solution is preferably 3.5 to 5 mol / L, more preferably 3.5 to 4 mol / L, and more preferably 3.5 mol / L.

[0053] In the present invention, the molar ratio of the persulfate to the strong base is preferably 1:35-50, more preferably 1:35-40, and more preferably 1:35.

[0054] In the present invention, the purpose of adding a mixed solution of persulfate and strong base is that persulfate helps to form needle-shaped substances, and strong base is the key to forming hydroxide. The mixture of the two helps to form Cu(OH)2 needle-shaped substances.

[0055] In the present invention, the temperature of the in-situ growth in step (2) is preferably room temperature; the time is preferably 10 to 15 minutes, more preferably 12 to 15 minutes, and more preferably 15 minutes.

[0056] In the present invention, after the in-situ growth in step (2), the step preferably further includes: washing and drying in sequence.

[0057] In the present invention, the washing agent is preferably water.

[0058] In the present invention, the drying temperature is preferably room temperature.

[0059] In the present invention, the Cu(OH)2 nanoneedles in the Cu(OH)2 / Cu heterostructure in step (2) are sea urchin-shaped; the length of the Cu(OH)2 nanoneedles is 5 to 20 μm and the diameter is 100 to 300 nm.

[0060] In the present invention, the reducing agent in step (3) preferably includes hydrazine hydrate or formaldehyde, and more preferably hydrazine hydrate.

[0061] In the present invention, the reducing agent in step (3) is preferably a mixture of a reducing agent and water.

[0062] In the present invention, the volume concentration of the reducing agent in step (3) is preferably 50 to 80 vt%, more preferably 50 to 60 vt%, and more preferably 50 vt%.

[0063] In the present invention, the temperature of the steam reduction in step (3) is preferably 60-80°C, more preferably 60-70°C, and more preferably 60°C; the time is preferably 15-60 min, more preferably 15-30 min, and more preferably 15 min.

[0064] The invention also provides a Cu-based nano-array catalyst prepared by the preparation method.

[0065] The present invention also provides an application of the Cu-based nano-array catalyst in preparing C2H4 by electrocatalytic reduction of CO2.

[0066] In the present invention, the application method is not limited, and any method known to those skilled in the art may be used.

[0067] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0068] Example 1

[0069] This embodiment provides a method for preparing a Cu-based nanoarray catalyst, comprising the following steps:

[0070] (1) CuSO4·5H2O, H2SO4, disodium EDTA, and PVP (average molecular weight 55000) were dissolved in deionized water to prepare 200 mL of electrolyte, wherein the concentration of CuSO4·5H2O was 0.2 mol / L, the concentration of H2SO4 was 1.5 mol / L, the concentration of disodium EDTA was 10 mmol / L, and the concentration of PVP was 10 g / L; 50 mL of the electrolyte was placed in a 50 mL beaker, and electrodeposition was performed using a two-electrode device, wherein a 1.5×3 cm 2 Copper mesh is anode, 1.5×3cm 2 YLS-30T carbon paper was used as the cathode, and a constant current of 250 mA was applied for electrodeposition. After 600 s, a gas diffusion electrode loaded with Cu was obtained, and the particle size of Cu was 0.5-2 μm.

[0071] (2) dissolving potassium persulfate in distilled water to prepare a first solution of 0.1 mol / L, and dissolving sodium hydroxide in distilled water to prepare a second solution of 3.5 mol / L; rapidly adding the second solution to the first solution at room temperature and stirring until the solution is clear, thereby obtaining a mixed solution having a molar ratio of potassium persulfate to sodium hydroxide of 1:35; rinsing the Cu-loaded carbon paper electrode obtained in step (1) with deionized water, immersing the electrode in the mixed solution at room temperature, taking it out after 15 minutes, rinsing it with deionized water, and drying it at room temperature, thereby obtaining a Cu(OH)2 / Cu heterostructure;

[0072] (3) The Cu(OH)2 / Cu heterostructure obtained in step (2) was reduced by hydrazine hydrate vapor reduction method, wherein the concentration of hydrazine hydrate was 50vt%, the reduction temperature was 60°C, and the reduction time was 15min, and finally a Cu-based nanoarray catalyst was obtained, which was recorded as Cu(OH)2@Cu2O / Cu-15.

[0073] The Cu(OH)2 / Cu heterostructure obtained in step (2) of Example 1 was characterized by scanning electron microscopy. The SEM results are as follows: Figure 1 As shown in the figure, it can be seen that Cu(OH)2 / Cu is in the shape of sea urchin and arranged neatly and orderly.

[0074] The Cu(OH)2@Cu2O / Cu-15 obtained in Example 1 was characterized by scanning electron microscopy. The SEM results are as follows: Figure 2 As shown in the figure, it can be seen that the Cu(OH)2@Cu2O / Cu-15 sea urchin needle structure remains intact as a whole, and the surface has obvious granularity.

[0075] The Cu(OH)2@Cu2O / Cu-15 array catalyst prepared in Example 1 was tested for its electrocatalytic CO2 reduction performance in a gas diffusion electrolytic cell using a 1 mol / L KOH solution as the electrolyte. The results are as follows: Figure 3 As shown, the catalyst prepared in Example 1 exhibits a C2H4 selectivity as high as 56%.

[0076] Example 2

[0077] This embodiment provides a method for preparing a Cu-based nanoarray catalyst. The difference from Embodiment 1 is that the reduction time in step (3) is changed to 60 min, and the other parameter conditions are the same as those in Embodiment 1, to obtain a Cu-based nanoarray catalyst, which is recorded as Cu2O / Cu-60.

[0078] The Cu2O / Cu-60 obtained in Example 2 was characterized by scanning electron microscopy. The SEM results are as follows: Figure 4As shown in the figure, it can be seen that the sea urchin needle structure of Cu2O / Cu-60 remains intact as a whole, and the surface granularity is more obvious than that of Cu(OH)2@Cu2O / Cu-15.

[0079] The Cu2O / Cu-60 catalyst prepared in Example 2 was tested for its electrocatalytic CO2 reduction performance in a gas diffusion electrolytic cell using a 1 mol / L KOH solution as the electrolyte. The results are as follows: Figure 5 As shown, the catalyst prepared in Example 2 exhibits a C2H4 selectivity of 38%.

[0080] The catalyst prepared in Example 1 was characterized by XRD. Figure 6 As shown. Figure 6 It can be seen that the present invention successfully achieves the deposition of copper (Cu) on a carbon substrate using electrodeposition technology. Further, through a chemical conversion process, part of the deposited copper is converted into Cu(OH)2. Finally, through a hydrazine hydrate vapor reduction method for 15 minutes, a partial conversion of Cu(OH)2 to Cu2O is achieved, thereby obtaining a structurally stable composite of Cu(OH)2 and Cu2O, namely Cu(OH)2@Cu2O / Cu.

[0081] Example 3

[0082] This embodiment provides a method for preparing a Cu-based nanoarray catalyst. The difference from Example 1 is that the reduction time in step (3) is changed to 30 min, and the other parameter conditions are the same as those in Example 1, to obtain a Cu(OH)2@Cu2O / Cu-30 nanoarray catalyst.

[0083] Example 4

[0084] This embodiment provides a method for preparing a Cu-based nanoarray catalyst. The difference from Example 1 is that the reduction time in step (3) is changed to 45 min, and the other parameter conditions are the same as those in Example 1, to obtain a Cu(OH)2@Cu2O / Cu-45 nanoarray catalyst.

[0085] The catalysts prepared in Examples 1 to 4 were characterized by XRD. Figure 7 As shown. Figure 7 It can be seen that the present invention controls the reduction time of hydrazine hydrate steam method, and performs reduction time of 15, 30, 45, and 60 minutes respectively, and Cu(OH)2 is gradually converted into Cu2O, until Cu(OH)2 is completely converted into Cu2O after 60 minutes of reduction, thereby obtaining the structure Cu2O / Cu.

[0086] Example 5

[0087] This embodiment provides a method for preparing a Cu-based nanoarray catalyst, comprising the following steps:

[0088] (1) CuSO 4· 5H2O, H2SO4, disodium EDTA, and PVP (average molecular weight 100,000) were dissolved in deionized water to prepare 200 mL of electrolyte, of which CuSO 4· The concentration of 5H2O is 0.1mol / L, the concentration of H2SO4 is 2mol / L, the concentration of disodium EDTA is 20mmol / L, and the concentration of PVP is 15g / L; 50mL of electrolyte is placed in a 50mL beaker, and electrodeposition is performed using a two-electrode device, with a 1.5×3cm 2 Copper mesh is anode, 1.5×3cm 2 YLS-30T carbon paper was used as the cathode, and a constant current of 200 mA was applied for electrodeposition. After 800 s, a gas diffusion electrode loaded with Cu was obtained, and the particle size of Cu was 0.8-2.5 μm.

[0089] (2) dissolving sodium persulfate in distilled water to prepare a first solution of 0.3 mol / L, and dissolving potassium hydroxide in distilled water to prepare a second solution of 5 mol / L; rapidly adding the second solution to the first solution at room temperature and stirring until the solution is clear, thereby obtaining a mixed solution having a molar ratio of sodium persulfate to potassium hydroxide of 1:40; rinsing the Cu-loaded carbon paper electrode obtained in step (1) with deionized water, immersing the electrode in the mixed solution at room temperature, taking it out after 10 min, rinsing it with deionized water, and drying it at room temperature, thereby obtaining a Cu(OH)2 / Cu heterostructure;

[0090] (3) The Cu(OH)2 / Cu heterostructure obtained in step (2) was reduced by formaldehyde vapor reduction method, wherein the formaldehyde concentration was 80vt%, the reduction temperature was 70°C, and the reduction time was 15min, and finally a Cu-based nanoarray catalyst was obtained, which was recorded as Cu(OH)2@Cu2O / Cu.

[0091] Example 6

[0092] This embodiment provides a method for preparing a Cu-based nanoarray catalyst, comprising the following steps:

[0093] (1) CuSO4·5H2O, H2SO4, disodium EDTA, and PVP (average molecular weight 40,000) were dissolved in deionized water to prepare 200 mL of electrolyte, wherein the concentration of CuSO4·5H2O was 0.3 mol / L, the concentration of H2SO4 was 1 mol / L, the concentration of disodium EDTA was 30 mmol / L, and the concentration of PVP was 12 g / L; 50 mL of the electrolyte was placed in a 50 mL beaker, and electrodeposition was performed using a two-electrode device, wherein a 1.5×3 cm 2 Copper mesh is anode, 1.5×3cm 2 YLS-30T carbon paper was used as the cathode, and a constant current of 220 mA was applied for electrodeposition. After 1000 s, a carbon paper electrode loaded with Cu was obtained, and the particle size of Cu was 1 to 3 μm.

[0094] (2) dissolving potassium persulfate in distilled water to prepare a first solution of 0.2 mol / L, and dissolving sodium hydroxide in distilled water to prepare a second solution of 4 mol / L; rapidly adding the second solution to the first solution at room temperature and stirring until the solution is clear, thereby obtaining a mixed solution having a molar ratio of potassium persulfate to sodium hydroxide of 1:50; rinsing the Cu-loaded carbon paper electrode obtained in step (1) with deionized water, immersing the electrode in the mixed solution at room temperature, taking it out after 12 minutes, rinsing it with deionized water, and drying it at room temperature, thereby obtaining a Cu(OH)2 / Cu heterostructure;

[0095] (3) The Cu(OH)2 / Cu heterostructure obtained in step (2) is reduced by hydrazine hydrate vapor reduction method, wherein the concentration of hydrazine hydrate is 60vt%, the reduction temperature is 80°C, and the reduction time is 15min, and finally a Cu-based nanoarray catalyst is obtained, which is recorded as Cu(OH)2@Cu2O / Cu.

[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Cu-based nanoarray catalyst, characterized in that: The following steps are involved: (1) In a dual-electrode system, a gas diffusion electrode is electrodeposited in a copper salt-containing electrolyte to obtain a Cu-loaded gas diffusion electrode; (2) immersing the Cu-loaded gas diffusion electrode of step (1) in a mixed solution of persulfate and strong alkali for in-situ growth to obtain a Cu(OH)2 / Cu heterostructure; (3) The Cu(OH)2 / Cu heterostructure described in step (2) is reduced by a steam method using a reducing agent to obtain a Cu-based nanoarray catalyst.

2. The preparation method according to claim 1, characterized in that: The composition of the copper salt electrolyte in step (1) includes: CuSO4·5H2O, H2SO4, PVP, disodium EDTA and water; wherein the concentration of CuSO4·5H2O is 0.1-0.3 mol / L, the concentration of H2SO4 is 1-2 mol / L, the concentration of disodium EDTA is 10-30 mmol / L, and the concentration of PVP is 10-15 g / L.

3. The preparation method according to claim 1 or 2, characterized in that: The dual-electrode system in step (1) is: the gas diffusion electrode is the working electrode, and the copper mesh is the counter electrode.

4. The preparation method according to claim 3, characterized in that: The current of the electrodeposition in step (1) is 200-250 mA, and the time is 600-1000 s.

5. The preparation method according to claim 1 or 4, characterized in that: In the mixed solution of persulfate and strong base in step (2), the persulfate includes potassium persulfate, ammonium persulfate or sodium persulfate, the strong base includes sodium hydroxide or potassium hydroxide, and the molar ratio of the persulfate to the strong base is 1:35-50.

6. The preparation method according to claim 5, characterized in that: The temperature of the in-situ growth in step (2) is room temperature and the time is 10 to 15 minutes.

7. The preparation method according to claim 1 or 6, characterized in that: The reducing agent in step (3) comprises hydrazine hydrate or formaldehyde, and the volume concentration of the reducing agent is 50 to 80 vt%.

8. The preparation method according to claim 7, characterized in that: The temperature of the steam reduction in step (3) is 60 to 80° C. and the time is 15 to 60 minutes.

9. The Cu-based nanoarray catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the Cu-based nanoarray catalyst according to claim 9 in the electrocatalytic reduction of CO2 to produce C2H4.